Makna Moral Dalam Muallaqah Zuhair Bin Abi Sulma: Studi Semiotika Roland Barthes/Moral Meanings in the Muallaqah of Zuhair Bin Abi Sulma: A Study based on Roland Barthes' Semiotics - Miftahul Mufid; Rohmanudin Rohmanudin; Nilna Indriana (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This study aims to uncover the moral meanings in Muallaqah Zuhair bin Abi Sulma using Roland Barthes' semiotic approach. Employing a qualitative literary research method, the analysis is conducted through Barthes' three-tiered framework of denotation, connotation, and myth. By applying these concepts, this research analyzes how values such as peace, generosity, honesty, and social responsibility are conveyed through the system of signs within the poem. Relevant verses were collected, categorized thematically, and examined through textual analysis to reveal interconnected layers of meaning textual, cultural, and normative. The findings indicate that Muallaqah Zuhair is not only a literary masterpiece but also a moral document reflecting the worldview of pre-Islamic Arab society. Each verse containing moral messages contributes to a collective myth, a unified ideological meaning that affirms a noble life is one built on dignity, peace, and virtue. This study offers a new perspective for understanding classical Arabic literature through the lens of modern semiotic theory.Penelitian ini bertujuan untuk mengungkap makna moral dalam Muallaqah Zuhair bin Abi Sulma dengan menggunakan pendekatan semiotika Roland Barthes. Dengan metode penelitian kualitatif studi literer, analisis dilakukan melalui kerangka tiga lapis makna Barthes: denotasi, konotasi, dan mitos. Penerapan konsep ini digunakan untuk menganalisis bagaimana nilai-nilai seperti perdamaian, kedermawanan, kejujuran, dan tanggung jawab sosial disampaikan melalui sistem tanda dalam puisi tersebut. Bait-bait relevan dikumpulkan, dikategorikan secara tematik, dan diteliti melalui analisis tekstual untuk mengungkap lapisan makna yang saling terhubung tekstual, budaya, dan normatif. Temuan penelitian menunjukkan bahwa Muallaqah Zuhair bukan hanya sebuah mahakarya sastra, tetapi juga dokumen moral yang merefleksikan pandangan dunia masyarakat Arab pra-Islam. Setiap bait yang mengandung pesan moral berkontribusi pada suatu mitos kolektif, sebuah makna ideologis terpadu yang menegaskan bahwa hidup yang mulia adalah hidup yang dibangun atas dasar martabat, perdamaian, dan kebajikan. Studi ini menawarkan perspektif baru untuk memahami sastra Arab klasik melalui lensa teori semiotika modern.